برامج الأطفال التلفزيونية... الواقع والوصفة - مراد, ميلود (University of Eloued جامعة الوادي, 2016)
تعتبر الطفولة مرحلة مهمة من مراحل حياة الإنسان، ويعد الإعلام الموجه للطفل من أهم أنواع الإعلام إذا نظرنا له من جانب التقسيم بالشريحة العمرية؛ فإن الشركات تعمل على أساس أن الطفل عالم قابل للتشكيل بحسب الرغبات والأهداف المقصودة، وأنه رهان كبير على المستقبل والحاضر. ويثير المختصون بعلوم التربية مشكلة التناقضات في مجموعة القيم والنظم السلوكية التي قد يتعرض لها الطفل في مبتدأ حياته مما يتسبب له بقلق نفسي واضطراب سلوكي، وليست وسائل الإعلام بمعزل عن هذه المشكلة، فنحن مدعون لمناقشة المواد المعروضة للطفل في التلفزيون ومدى إسهامها في خلق جيل قوي متشبث بعادات وتقاليد أسلافه وهذا بالعناية بنوعية التربية التي يتلقاها أطفالنا. ABSTRACT: Childhood is an important stage of human life, a child-oriented media is one of the most important types of media if we look at him of side of the slice division age. The companies are working on the basis that the child moldable world according to the desires and goals intended, and it is a big bet on the future and the present. Science education specialists raises the problem of the contradictions in a range of behavioral and systems values that the child might be exposed at the beginning of his life, causing him anxiety and behavioral disorder. The media is not apart from this problem, we need to discuss the programs offered for children on television and their contribution to the creation of a strong generation clinging customs and traditions of his ancestors through attention to the quality of education received by our children
Children's television programs
مجلة البحوث والدراسات المجلد 13 العدد 02 جامعة الوادي
Keywords: الإعلام- البرامج- الأطفال- التربية- التلفزيون; Media - Programs - Children - Education - Television.